Analisis Faktor Penyebab Ketidaktepatan Kode Diagnosis Penyakit Diabetes Mellitus di Rumah Sakit Umum Haji Surabaya - Errica Rostia Loren; Rossalina Adi Wijayanti; Nikmatun Nikmatun (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The accuracy of determining the disease diagnosis code is one of the important things that must beconsidered in carrying out the coding process of the patient's disease diagnosis made by the coder. Theaccuracy and inaccuracy of providing disease diagnosis codes will affect data and information in the healthservice process and reduce the quality of services in hospitals. Besides, in the era of National HealthInsurance (JKN), the accuracy of the diagnosis code was also very influential in financing at hospitals. Thisresearch was aimed to analyze the factors which cause the diagnosis code inaccuracy in Diabetes Mellitus inSurabaya Hajj General Hospital in 2019. This research used qualitative methods with data collectiontechniques such as interviews, observation, and literature studies. The number of samples used in the studywas 21 medical records of Diabetes Mellitus patients and 2 informants. The results of research on the medicalrecord documents of patients with Diabetes Mellitus found that the documents have an incorrect code of 13medical record documents (62%) and documents that have an exact code of 8 medical record documents(38%). The results of the analysis found were several factors that influence the inaccuracy of the code such ascoder's competency, coder's knowledge, as well as the experience of coder and medical record document,both the completeness of the filling and the documentation. The solution that can be proposed by theresearcher is to included the coder and medical personnel in training and outreach related to thedetermination of diagnosis code, especially Diabetes Mellitus.